PM10 air pollution and acute hospital admissions for cardiovascular and respiratory causes in Ostrava - Tomášková, Hana; Tomášek, Ivan; Šlachtová, Hana; Polaufová, Pavla; Šplíchalová, Anna; Michalík, Jiří; Feltl, David; Lux, Jaroslav; Marsová, Marie (Central European Journal of Public Health, 2016)
BACKGROUND: The city of Ostrava and its surroundings belong to the most long-therm polluted areas in the Czech Republic and Europe. For identification of health risk, the World Health Organization recommends a theoretical estimation of increased short-term PM10 concentrations effect on hospital admissions for cardiac complaints based on a 0.6% increase per 10 µg.m(-3) PM10 and 1.14% increase for respiratory causes. The goal of the present study is to verify the percentage increase of morbidity due to cardiovascular and respiratory causes, as per WHO recommendations for health risk assessment, in the population of Ostrava. METHODS: The input data include data on PM10 air pollution, meteorological data, the absolute number of hospital admissions for acute cardiovascular and respiratory diseases in the period 2010-2012. To examine the association between air pollution and health outcomes the time series Poisson regression adjusted for covari-ates was used. RESULTS: A significant relationship was found between the cardiovascular hospital admissions (percentage increase of 1.24% per 10 µg.m(-3)) and values of PM10 less than 150 µg.m(-3) in the basic model, although after adjustment for other factors, this relationship was no longer significant. A significant relationship was also observed for respiratory causes of hospital admissions in the basic model. Contrary to cardiovascular hospitalization, the relationship between respiratory hospital admissions and PM10 values below 150 µg.m(-3) (percentage increase of 1.52%) remained statistically significant after adjustment for other factors. CONCLUSIONS: The observed significant relationship between hospital admissions for respiratory causes was consistent with the results of large European and American studies.
Keywords: Infant, Newborn; látky znečišťující vzduch; počasí; mužské pohlaví; Male; Czech Republic; senioři; senioři nad 80 let; Weather; Respiratory Tract Diseases; pevné částice; Female; Humans; novorozenec; kojenec; Particulate Matter; lidé; Middle Aged; ženské pohlaví; analýza přerušované časové série; lidé středního věku; průmysl; Infant; Acute Disease; znečištění ovzduší; Česká republika; mladiství; akutní nemoc; kardiovaskulární nemoci; vystavení vlivu životního prostředí; Environmental Exposure; Aged, 80 and over; dítě; Child; Interrupted Time Series Analysis; Adolescent; Air Pollutants; Hospitalization; Child, Preschool; dospělí; Adult; nemoci dýchací soustavy; předškolní dítě; Air Pollution; Aged; Industry; Cardiovascular Diseases; hospitalizace